POS5 Gene of Saccharomyces cerevisiae Encodes a Mitochondrial NADH Kinase Required for Stability of Mitochondrial DNA - Strand, Micheline K. (American Society for Microbiology, 2003)
In a search for nuclear genes that affect mutagenesis of mitochondrial DNA in Saccharomyces cerevisiae, an ATP-NAD (NADH) kinase, encoded by POS5, that functions exclusively in mitochondria was identified. The POS5 gene product was overproduced in Escherichia coli and purified without a mitochondrial targeting sequence. A direct biochemical assay demonstrated that the POS5 gene product utilizes ATP to phosphorylate both NADH and NAD(+), with a twofold preference for NADH. Disruption of POS5 increased minus-one frameshift mutations in mitochondrial DNA 50-fold, as measured by the arg8(m) reversion assay, with no increase in nuclear mutations. Also, a dramatic increase in petite colony formation and slow growth on glycerol or limited glucose were observed. POS5 was previously described as a gene required for resistance to hydrogen peroxide. Consistent with a role in the mitochondrial response to oxidative stress, a pos5 deletion exhibited a 28-fold increase in oxidative damage to mitochondrial proteins and hypersensitivity to exogenous copper. Furthermore, disruption of POS5 induced mitochondrial biogenesis as a response to mitochondrial dysfunction. Thus, the POS5 NADH kinase is required for mitochondrial DNA stability with a critical role in detoxification of reactive oxygen species. These results predict a role for NADH kinase in human mitochondrial diseases.